Phenylthiourea synergistically enhances the hepatotoxicity of bavachalcone by interfering with metabolism in zebrafish: A factor to consider when evaluating toxicity of environmental pollutants using zebrafish models - Te Zheng; Jingcheng Zhao; Chenglong Sun; Chengyue Zhu; Chenqinyao Li; Jiashuo Zhou; Jing Yang; Yun Zhang (Ecotoxicology and Environmental Safety)
Phenylthiourea (PTU) is a well-known inhibitor of melanin synthesis that has been extensively utilized in ecotoxicological studies involving zebrafish. Although there are reports suggesting that PTU may influence the toxicity of various compounds, the underlying mechanisms of its action remain unclear. Bavachalcone (BavaC) has a wide range of applications in agriculture and medicine, and it can enter groundwater through a variety of pathways that may pose a risk to aquatic ecosystems. We found that PTU enhanced the hepatotoxicity of BavaC in zebrafish, but the mechanism was unclear. In this study, the interactive effects of 200 μM PTU and 2.5 μM BavaC on the toxicity of zebrafish larvae were evaluated after 72 h of exposure. PTU significantly increased BavaC-induced hepatotoxicity, which was characterized by liver hypoplasia, hepatocyte vacuolation, and lipid accumulation. Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI) revealed that the contents of fatty acids, phosphatidylcholine and glutathione significantly increased. The results of RNA sequencing (RNA-seq) and Real-time PCR (RT-qPCR) analyses indicated that several metabolic pathways, including xenobiotic biodegradation and metabolism, amino acid metabolism, lipid metabolism and carbohydrate metabolism, were differentially regulated in the PTU+BavaC group compared to the BavaC group. Our findings indicate that PTU-induced metabolic disorders exacerbate BavaC hepatotoxicity and highlight the need to reconsider the use of PTU in zebrafish-based toxicity assessments of environmental pollutants.